2009
DOI: 10.1109/tmi.2009.2016212
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Estimation Method for Physiological Parameters in Dynamic Contrast-Enhanced MRI: Application of a Distributed Parameter Model Using Fourier-Domain Calculations

Abstract: Dynamic contrast-enhanced magnetic resonance imaging (MRI) is a promising tool in the evaluation of tumor physiology. From rapidly acquired images and a model for contrast agent pharmacokinetics, physiological parameters are derived. One pharmacokinetic model, the tissue homogeneity model, enables estimation of both blood flow and vessel permeability together with parameters that describe blood volume and extracellular extravascular volume fraction. However, studies have shown that parameter estimation with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
47
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(49 citation statements)
references
References 22 publications
2
47
0
Order By: Relevance
“…The above DP models have been previously used in DCE CT studies of various tumors (8)(9)(10)(11)65,68) and are gaining popularity in DCE MRI (73)(74)(75)(76)(77)(78)(79). However, recent studies have raised concerns about the presence of discontinuities in the impulse residue functions of DP models which could result in convergence problems during fitting, leading to reduced parameter precision (75,(77)(78)(79).…”
Section: Distributed Parameter (Dp) Models and Variationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The above DP models have been previously used in DCE CT studies of various tumors (8)(9)(10)(11)65,68) and are gaining popularity in DCE MRI (73)(74)(75)(76)(77)(78)(79). However, recent studies have raised concerns about the presence of discontinuities in the impulse residue functions of DP models which could result in convergence problems during fitting, leading to reduced parameter precision (75,(77)(78)(79).…”
Section: Distributed Parameter (Dp) Models and Variationsmentioning
confidence: 99%
“…However, recent studies have raised concerns about the presence of discontinuities in the impulse residue functions of DP models which could result in convergence problems during fitting, leading to reduced parameter precision (75,(77)(78)(79). It is explained in Ref.…”
Section: Distributed Parameter (Dp) Models and Variationsmentioning
confidence: 99%
“…The closed-form model solution exists only in the Laplace space [205]. According to Garpebring et al [206], the TH solution could be found with the fast Fourier transform. This approach removes many practical obstacles to using the TH in DCE-MRI analysis [70].…”
Section: B Tissue Homogeneity (Th) Modelmentioning
confidence: 99%
“…However, the TH estimation is somewhat difficult and slow even with the AATH, due to a large number of initial guesses in order to avoid too large parameter values [207]. Also, the increased computational cost if voxel-wise parametric maps are needed hinders the wider use of the model [206].…”
Section: B Tissue Homogeneity (Th) Modelmentioning
confidence: 99%
See 1 more Smart Citation